Anti-HIV activity of methanolic and aqueous extracts of fifteen materials of beach-cast macroalgae: valorization of underused waste biomass. Issue 1 (31st December 2022) - Harb, Talissa Barroco; Chow, Fungyi
ABSTRACT: Beach-cast seaweeds are unexplored feedstock with plentiful biomass in some localities that could be exploited as important sources of natural products. This study evaluated the potential of beach-cast seaweed extracts to inhibit the reverse transcriptase enzyme of the HIV-1. In general, the aqueous extracts showed better biotechnological potential as an antiviral agent than methanolic extracts with lower values of IC50 . However, both extracts from Alsidium seaforthii, Osmundaria obtusiloba, Dictyopteris jolyana, and Zonaria tournefortii were highly promising, reaching inhibition above 90%, as well the aqueous extract of Spyridia clavata . Macroalgae are characterized by high levels of sulphated polysaccharides, such as the carrageenan and agar sulphated galactans in red algae, fucans and fucoidans in brown algae, and heterofucans in green algae, which have been related to antiviral biological activity. Furthermore, polyphenols and tannins have been reported as the main metabolites responsible for high antiviral activity in methanol extracts from red and brown algae. One or a combination of these compounds could explain our findings. Nowadays, there is a demand in the industrial and pharmaceutical sectors for natural products with potential bioactivity and beach-cast seaweeds could be a renewable, economically viable, and abundant resource for biotechnological approaches. Therefore, this research could help multiple UN SDGs as 1 (no poverty), 3 (good health and well-being), 5 (gender equality), 6 (clean water and sanitation), 8 (decent work and economic growth), 9 (industry, innovation, and infrastructure), 10 (reduced inequalities), 11 (sustainable cities and communities), 12 (responsible consumption and production), 13 (climate action), 14 (life below water), 17 (partnerships for the goals) through the integration of sustainable use of marine resources benefiting local communities, especially female equality, human and ecosystem health and sustainable consumption and development.